The Influence of Transaction Recording Habits, Financial Literacy, and Budget Management on Individual Finances - Felicia Ivanachen; Evelyna Utomo; Jholant Bringg Luck Amelia Br Sinaga; Munawarah, Munawarah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aimed to analyze the impact of transaction recording habits, financial literacy, and budget management on individual finances. This study employed a quantitative approach through a survey of 41 respondents, with 37 samples meeting the criteria. Data were obtained through a Likert-scale questionnaire and processed using IBM SPSS Statistics 25. The data processing revealed that transaction recording habits, financial literacy, and budget management simultaneously had a significant impact on individual financial conditions. Partially, the transaction recording habit variable was the only one that did not show a significant impact.